2020
DOI: 10.1108/pr-03-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Beyond quid pro quo: good soldiers and characteristics of their helping behaviours

Abstract: PurposeGood soldiers are people who engage in citizenship behaviors “to do good” instead of “to look good”. The purpose of this article is to explore the motivations behind and the specific characteristics of behaviours of the good soldiers in the context of work using social exchange theory (SET) as a theoretical framework.Design/methodology/approach A total of 47 dyadic interviews with 94 individuals from three organisations where good soldiers are most likely to be observed were conducted.FindingsData analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…This is also aligned with an argument that strategies that are commonly used for motivating neurotypical employees (e.g. O'Donoghue and van der Werff, 2021; Szulc, 2020), may not resonate well with their neurominorities counterparts (Parr et al. , 2013).…”
Section: Literature Reviewsupporting
confidence: 63%
“…This is also aligned with an argument that strategies that are commonly used for motivating neurotypical employees (e.g. O'Donoghue and van der Werff, 2021; Szulc, 2020), may not resonate well with their neurominorities counterparts (Parr et al. , 2013).…”
Section: Literature Reviewsupporting
confidence: 63%
“…Work environment should be also designed in a way that gives neurodivergent individuals feelings of relatedness to maintain motivation. Indeed, caring workplace relationships are known to enhance well-being (Szulc, 2020) and work is portrayed as an opportunity for positive social interaction for neurodivergent employees through day-to-day communication and ad-hoc social events (Hedley et al , 2018), especially in small-group settings (Dreaver et al , 2020). Finally, research emphasised the role of positive reinforcement on the motivation of neurodivergent individuals (Müller et al , 2003).…”
Section: Motivationmentioning
confidence: 99%
“…Finally, we found that furloughed individuals often considered their skills to be inferior to the skills of their non-furloughed colleagues. This may lead to low self-esteem and confidence problems (Shack et al, 2018 ) which, if not addressed, may influence overall organizational climate by diving the workforce and negatively affecting their relationships (Szulc, 2020 ). Consistently, employers may consider implementing return-to-work interviews where employee's value and contribution to the organization is emphasized.…”
Section: Discussionmentioning
confidence: 99%